2018
DOI: 10.1002/ejoc.201801249
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on the Reactivity of the 2,4,6‐Tridehydropyridinium Cation, an Aromatic σ,σ,σ‐Triradical

Abstract: 2,4,6-Tridehydropyridinium cation (7) undergoes three consecutive atom or atom group abstractions from reagent molecules in the gas phase. By placing a π-electron-donating hydroxyl group between two radical sites, their reactivity can be quenched by enhancing their through-space coupling via a favorable resonance structure. Indeed, 3-hydroxy-2,4,6-tridehydropyridinium cation (8) abstracts only one atom or group of atoms from reagents. On the other hand, an electron-withdrawing cyano group between two of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…The analogous tri‐ and tetraradicals containing meta ‐benzyne moieties should be even more interesting due to their complex electronic structures, which have inspired some theoretical studies on the triradicals . However, due to extreme difficulties in studying these species experimentally, the reactivity of only three such triradicals (2,4,6‐tridehydro‐, 3‐hydroxy‐2,4,6‐tridehydro‐, and 3‐cyano‐2,4,6‐tridehydropyridinium cations) and one tetraradical (2,4,6‐tridehydropyridine radical cation) has been studied thus far and only in the gas phase . Unlike the triradicals, the tetraradical was found not to undergo radical reactions .…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…The analogous tri‐ and tetraradicals containing meta ‐benzyne moieties should be even more interesting due to their complex electronic structures, which have inspired some theoretical studies on the triradicals . However, due to extreme difficulties in studying these species experimentally, the reactivity of only three such triradicals (2,4,6‐tridehydro‐, 3‐hydroxy‐2,4,6‐tridehydro‐, and 3‐cyano‐2,4,6‐tridehydropyridinium cations) and one tetraradical (2,4,6‐tridehydropyridine radical cation) has been studied thus far and only in the gas phase . Unlike the triradicals, the tetraradical was found not to undergo radical reactions .…”
Section: Introductionsupporting
confidence: 57%
“…Briefly, its tetraiodo precursor was protonated in an atmospheric‐pressure chemical ionization source, the ions were isolated in the LQIT by ejecting all unwanted ions, and the iodine atoms were cleaved off by collision‐activated dissociation. Previous studies have demonstrated that the radical sites created in this manner in aromatic systems do not undergo rearrangement . The structures of all radical species were verified by using well‐established structurally diagnostic reactions, as described previously .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations